T-Cell Depleted Haploidentical Transplantation in Children With Hematological Malignancies: A Comparison Between CD3+/CD19+ and TCRαβ+/CD19+ Depletion Platforms - Gonzalez-Vicent, Marta; Molina, Blanca; Lopez, Ivan; Zubicaray, Josune; Ruiz, Julia; Vicario, Jose Luis; Sebastián, Elena; Iriondo, June; Castillo, Ana; Abad, Lorea; Ramirez, Manuel; Sevilla, Julian; et al. (Frontiers in Oncology, 2022)
Background: T-cell depleted (TCD) haploidentical transplantation using CD3+/CD19+ and TCRαβ+/CD19+ depletion techniques have been increasingly used in children with hematological malignancies. We present a retrospective study aimed to compare transplant outcomes in children with leukemia receiving a TCD haploidentical transplant using either CD3+/CD19+ or TCRαβ+/CD19+ platforms. Methods: A total of 159 children with leukemia (ALL=80) (AML=79) that received a TCD haploidentical transplantation using either CD3+/CD19+ (n=79) or TCRαβ+/CD19+ (n=80) platforms between 2005 and 2020 were included. Median age was 9 years in both groups. There were no differences in patient, donor and transplant characteristics between groups except for donor KIR B genotype more frequent in TCRαβ+/CD19+ group (91%) than in CD3+/CD19+ group (76%) (p=0.009) and high number of NK+ cells and lower CD19+ cells infused in TCRαβ+/CD19+ group (35.32x106/kg and 0.06 x106/Kg) than in CD3+/CD19 group (24.6x106/Kg and 0.25 x106/Kg), (p=0.04 and p=0.0001) respectively. Conditioning was based in TBF. Median follow-up for survivors was 11 years (range; 8-16 y) in CD3+/CD19+ group and 5 years (range; 2-9 y) in TCRαβ+/CD19+ group. Results: Engraftment kinetics were similar in both groups (13 days for neutrophils and 10 days for platelets). There was no difference in the incidence of acute GvHD II-IV (29±5% in CD3+/CD19+ group vs 38±5% TCRαβ+/CD19+ group) and chronic GvHD (32±5% vs 23±4%, respectively). NRM was 23±5% in CD3+/CD19+group vs 21±4% in TCRαβ+/CD19+group. Relapse incidence was also similar 32±5% vs 34±6%, respectively. DFS and OS were not different (45±5% vs 45±6% and 53±6% vs 58±6%), respectively. As there were no differences on transplant outcomes between groups, we further analyzed all patients together for risk factors associated with transplant outcomes. On multivariate analysis, we identified that early disease status at transplant (HR: 0.16; 95%CI (0.07-0.35) (p=0.0001), presence of cGvHD (HR: 0.38; 95%CI (0.20-0.70) (p=0.002) and donor KIR-B genotype (HR: 0.50; 95%CI (0.32-0.90) (p=0.04) were associated with better DFS. Conclusions: Our data suggest that there are no advantages in transplant outcomes between TCD platforms. Risk factors for survival are dependent on disease characteristic, donor KIR genotype and chronic GvHD rather than TCD platform used.